Strategies of Socially Responsible Online Markrting and Advertising Management of Trade Enterprises Economic Affairs - Ustik T., Morokhova V., Savras I., Golda N.,Lukhanina K. and Sidielnikov D. (AESSRA, 2023)
Social aspects are increasingly taken into account in the marketing activities of enterprises, as they allow for solving many problems and increasing business profitability. The article aims to empirically study how the strategies of socially responsible online marketing and advertising management of trade enterprises ensure the efficiency of their activities. The research methodology includes case studies based on the case method of foreign trading companies - representative offices in Ukraine, which implement strategies of socially responsible online marketing and advertising management. The results demonstrate the integration and coherence of socially responsible marketing strategies following the problems and marketing activities of enterprises. Market positioning, niche features, product range, and marketing determine the purpose and objectives of online marketing strategies. Trade enterprises in the course of marketing products on the Internet face some problems that require the involvement of experts. As the analysis of the cases showed, independently developed strategies and advertising campaigns are not effective enough due to a lack of professional knowledge in advertising management of digital marketing. Socially responsible Internet marketing strategies contain the following main components: (1) purpose, goals, and objectives, coordinated with the overall strategy of enterprises; (2) strategic directions and tools for implementing the strategy; (3) key performance indicators, selected following the goals and objectives, which provide a measurement of the effectiveness of advertising management. The theoretical and practical value of the article lies in empirical confirmation of the need of enterprises in social marketing activities, which contributes to the growth of profits, formation of brand awareness, improvement of its reputation in the market, raising consumer awareness of products, taking into account the motives and interests of customers
Economic Affairs.- Vol. 68.-No. 01s.-2023
Keywords: strategy; marketing; advertising of the enterprise